A nomogram predicting the risk of postoperative pneumonia after esophagectomy in esophageal carcinoma - Chen, Binlie; Ke, Weiqi; Li, Meizhen (Frontiers in Medicine, 2025)
BackgroundPneumonia is a common complication following esophagectomy, which is related with an increased risk of mortality and hospitalization. This condition not only prolongs hospital stays but also raises healthcare costs. The aim of this study was to identify risk variables and develop a nomogram for predicting postoperative pneumonia (PP).MethodsA total of 647 individuals who had esophageal cancer surgery between January 1, 2010, and December 31, 2020, were involved in this study. We used least absolute shrinkage and selection operator (LASSO) regression for screening the optimal predictive factors and subsequently developed a nomogram using the selected factors. Verification through the use of 500 bootstrap resampling techniques. To assess the nomogram’s discriminating power, we used the calibration plot, receiver operating characteristic (ROC) curve, and decision curve analysis (DCA).ResultsAccording to the standard error criteria of non-zero coefficients of LASSO and multivariate logistic regression analyses, age, smoking, double-lumen endotracheal tube (DLET), combined intravenous and inhalation anesthesia (CIIA), and vasoactive drugs usage are independent risk indicators of PP. Based on these five predictors we created a nomogram. The area under the of nomogram for the ROC curve was 0.665 (95% CI: 0.620–0.704) in development and 0.691 (95%CI: 0.654–0.726) in 500 bootstraps resample validation. Additionally, the calibration curves showed a high degree of agreement between the actual and predicted probabilities. DCA displayed that the predictive model had a net benefit when the risk thresholds were 0.17–0.61.ConclusionThis study developed an intuitive nomogram model to predict postoperative pneumonia in esophageal cancer patients based on age, smoking history, DLET, CIIA, and vasoactive medication usage. Proper anesthesia, ETT type, smoking cessation, and timely vasoactive medication use can lower risks. Further external validation and large-scale studies are needed.